2021
DOI: 10.1007/s11523-021-00809-2
|View full text |Cite
|
Sign up to set email alerts
|

Bintrafusp Alfa, a Bifunctional Fusion Protein Targeting TGF-β and PD-L1, in Patients with Esophageal Adenocarcinoma: Results from a Phase 1 Cohort

Abstract: Background Esophageal adenocarcinoma patients have limited treatment options. TGF-β can be upregulated in esophageal adenocarcinoma, and blocking this pathway may enhance clinical response to PD-(L)1 inhibitors. Bintrafusp alfa is a firstin-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β "trap") fused to a human IgG1 mAb blocking PD-L1. Objective The objective of this study was to investigate the efficacy and safety of bintrafusp alfa in patients with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The investigator-assessed and independent review-confirmed overall response rate (ORR) was 13.3% and 20%, respectively, with 83% of responses occurring in tumors with an immune-excluded phenotype. 36 Nineteen patients (63%) had TRAEs, with seven having grade 3 events. In a cohort in Asia in patients with esophageal squamous cell carcinoma investigator-assessed confirmed ORR rate and independent review, ORR was 20% and 10%, respectively.…”
Section: Clinical Applications Of Bintrafusp Alfamentioning
confidence: 99%
“…The investigator-assessed and independent review-confirmed overall response rate (ORR) was 13.3% and 20%, respectively, with 83% of responses occurring in tumors with an immune-excluded phenotype. 36 Nineteen patients (63%) had TRAEs, with seven having grade 3 events. In a cohort in Asia in patients with esophageal squamous cell carcinoma investigator-assessed confirmed ORR rate and independent review, ORR was 20% and 10%, respectively.…”
Section: Clinical Applications Of Bintrafusp Alfamentioning
confidence: 99%
“…Results from 2 phase 1 studies (NCT02517398 and NCT02699515) of > 670 patients treated with bintrafusp alfa demonstrated promising clinical activity in various expansion cohorts of advanced solid tumors [ 90 , 120 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Durable responses of > 6 months were reported in multiple advanced solid tumor types, and response rates were compared favorably with historical data for anti‐PD‐(L)1 therapies in the same tumor type, although no head‐to‐head studies have been conducted.…”
Section: Treatment Strategies For the Dual Inhibition Of Tgf‐β And Pd‐l1mentioning
confidence: 99%
“…In patients with advanced esophageal adenocarcinoma and esophageal squamous cell carcinoma, bintrafusp alfa shows clinical antitumor efficacy with a manageable safety profile. In patients with esophageal adenocarcinoma, the confirmed objective response rate is 20.0% (NCT02517398) [ 230 ]. Similarly, the confirmed objective response rate is 10.0% in patients with esophageal squamous cell carcinoma, with a median overall survival of 11.9 months (NCT02699515) [ 231 ].…”
Section: Therapies Based On Tgf-β Signal Transduction In Diseasementioning
confidence: 99%